Hailey-Hailey disease: a widespread abnormality of cell adhesion. - Burge, S; Millard, P; Wojnarowska, F (1991)
Suction has been used to investigate cell adhesion in clinically normal skin in Hailey-Hailey disease. We have demonstrated that there is a widespread subclinical abnormality in keratinocyte adhesion in this disease. There may be a synthesis of functionally deficient adhesion junctions, increased breakdown of adhesion junctions or abnormalities in other adhesion proteins in the epidermis in Hailey-Hailey disease. The findings contrast with those in Darier's disease in which abnormal cell adhesion was only demonstrable in clinically involved skin.